Building Condition Assessment and Preventive Maintenance of the Old Shophouses in Raub, Pahang - Chea Xian Wei (Research in Management of Technology and Business, 2021)
The survival of any building is underpinned by regular maintenance. On the other hand, regular maintenance is critical to any building, whether it’s heritage or non-heritage. There is crucial need to manage and ensuring the best maintenance of old shophouses. Therefore, maintenance has been identified as a key intervention in protecting old shophouses structure by prolonging a building lifespan. If there is no systematic and correct maintenance method, the old shophouses will deteriorate and will not be able to function as well. This study aims to identify the building maintenance and problems faced by old shophouses and to analyse the current preventive action on maintaining the old shophouses located in Raub, Pahang. Qualitative approach adopted for this research couple with the survey methodology for data gathering. In addition, data collection was obtained by observation and through interview with tenants of old shophouses. The study has found that the way to reduce defects of old shophouses and the impact of preventive maintenance are crucial. The results were examined by Building Condition Assessment (BCA) and it has provided a basis for the best maintenance plan for the old shophouses. Consequently, this study proposes a method to ensure high-quality of maintenance with regards to old shophouses conservation.